Possible Involvement of HSP90-HSF1 Multichaperone Complex in Impairment of HSP72 Induction in the Failing Heart Following Myocardial Infarction in Rats - Tetsuro Marunouchi; Masato Araki; Mao Murata; Norio Takagi; Kouichi Tanonaka (Elsevier, 2013)
It is generally accepted that an increase in the myocardial level of heat-shock protein 72 (HSP72) protects viable cardiac tissue against myocardial infarction (MI)-induced stress. However, the induction of HSP72 after exposure to heat shock (HS) is blunted in the failing rat heart following MI. The mechanisms underlying this impairment in the HSP72 induction ability of the failing heart are not yet clearly defined. In the present study, we examined the involvement in heat-shock factor 1 (HSF1), a transcription factor of HSPs, in decreased ability for HSP72 induction in the failing rat heart following MI. In the failing heart, nuclear translocation of the HSF1 after exposure to hyperthermia was markedly reduced, whereas HSF1 in the cytosolic fraction and the HSP90 chaperone complex containing HSF1, a repressor of HSF1, were increased. Treatment with an HSP90 inhibitor, 17-allylamino-17-demethoxygel-danamycin, appeared to dissociate the interaction of HSF1 with HSP90, and then induced HSP72 in the failing heart after exposure to hyperthermia. These results suggest that an increase in the multichaperone complex, especially the HSF1-HSP90 interaction, associated with attenuation of HSF1 translocation into the nucleus, was involved in the impairment of HS-induced HSP72 induction in the failing heart following MI. Keywords:: chronic heart failure, heat-shock factor-1, heat-shock protein 72, heat-shock protein 90, multichaperone complex